FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN GARMEN DAN TEKSTIL DI BEI - Karina Yuriska H, Hendro Lukman (Jurnal Paradigma Akuntansi, 2020)
The objective of this research is to obtain empirical evidence about the effect of EPS, Profitability and Current Ratio toward Share Price. This research uses secondary data. The object of this research is garment and textile companies listed in the Indonesia Stock Exchange (IDX) during the year 2014-2018. This research is conducted with 16 garment and textile companies as the sample. Furthermore, data collection techniques used in this research is purposive sampling that is processed using Statistical Package for the Social Sciences (SPSS) ver 24.0 program. The results of this research show that EPS has a significant effect toward Share Price, at the same time Profitability and Current Ratio do not have significant effect toward Share Price